Highly skin-conformal wearable tactile sensor based on piezoelectric-enhanced triboelectric nanogenerator. (October 2019) - Yu, Junbin; Hou, Xiaojuan; Cui, Min; Zhang, Shengnan; He, Jian; Geng, Wenping; Mu, Jiliang; Chou, Xiujian
Abstract: Highly skin-conformal wearable tactile sensors with high sensitivity and wide measurement range are promising for physiological signal monitoring, personalized recognition and human-machine interaction. In this paper, we report a hybrid piezoelectric-triboelectric sensor (HPTS) primarily composed of polarized micro-frustum-arrays structure lead-zirconate-titanate and polydimethylsiloxane (PZT&PDMS) composite film (m-PZT&PDMS) and m-Cu film, which can simultaneously generate the coupling of piezoelectric effect and triboelectrification by the contact-separation working mode. Combining the hybrid effect, micro-frustum-arrays structure and high piezoelectric constant material, the HPTS presents excellent sensitivity and wide measurement range. The HPTS can reach a sensitivity of 15.43 V/kPa when triboelectric effect performs in the pressure of 0 kPa–100 kPa, and 18.96 V/kPa when both the piezoelectric and triboelectric effects work in the pressure range of 100 kPa–800 kPa. In addition, the HPTS is largely based on the PZT&PDMS film being directly in contact with the skin, showing excellent skin-conformal characteristic. It also demonstrates good linearity, fast response time and high stability. These characteristics are attractive for sensing radial artery wave, monitoring the slide and touch of a finger, and detecting the strong pressure of limb movement. Hence, this work provides a new strategy by applying a highly skin-conformal piezoelectric-enhanced triboelectric nanogenerator with high sensitivity and wide measurement range as a wearable tactile sensor, exhibiting immense potential in medical research, personalized recognition and human-machine interaction. Graphical abstract: Based on the contact-separation working mode, the highly skin-conformal piezoelectric-enhanced triboelectric nanogenerator was fabricated with excellent sensitivity (18.96 V/kPa) and wide measurement range (0 kPa–1300 kPa), which presents immense potential in medical research, personalized recognition and human-machine interaction.Image 1 Highlights: Due to the use of m-PZT&PDMS film as the main body, the HPTS is able to provide more conformal and comfortable contact with irregular human skin and withstand complex deformations. The developed hybrid nanogenerator has high flexibility, excellent sensitivity and wide measurement range. The polarized m-PZT&PDMS film exhibits excellent output performance because the high piezoelectric modulus of PZT nanofibers, high weight ratio of PZT to PDMS and the optimized polarization parameters. The highly-conformal HPTS shows the high sensitivity (18.96 V/kPa) and wide measurement range (0 kPa–1, 300 kPa) to reliably and simultaneously detect weak and strong external forces in real-time, such as pulse waves and body movements.